The validity of a dual-force plate for assessing counter-movement jump performance - Mao, C.; Li, M.; Li, X.; Li, Z.; Liu, T.; Wang, L.; Zhu, W.; Chen, L.; Sun, Y. (Sensors, 2024)
The objective of this study was to assess the concurrent validity of the Kunwei force plate system in relation to variables during a counter-movement jump (CMJ) task, in comparison to the Kistler in-ground force plate system, which is considered the "gold standard". Methods: In a single testing session, the Kunwei force plates were placed directly on top of the in-ground Kistler force plate. This allowed for the simultaneous collection of vertical ground reaction forces from 30 participants (male, age = 22.8 ± 2.8 years, body mass = 74.3 ± 12.3 kg, height 178.2 ± 4.6 cm) during CMJ tests. The consistency between force plate systems was assessed using ordinary least products regression (OLPR) with bootstrapped 95% confidence intervals and the Interclass Correlation Coefficient (ICC). Results: There was no fixed or proportional bias in the CMJ variables measured between the force plate systems. The variables exhibited a strong correlation across the force plates during the CMJ task (ICC > 0.950, p < 0.01). Conclusion: The findings of this study indicate that there was no statistical difference between the Kunwei and Kistler force plate systems when evaluating common CMJ strategy and outcome variables, which are considered the gold standard. Hence, the Kunwei force plate can be regarded as a reliable substitute for the established industry benchmark in evaluating the force-time characteristics of the CMJ. Researchers, athletes, and coaches have the option to utilize this affordable and portable choice as a substitute for the more expensive laboratory-based force plate system. This alternative allows for the precise measurement of CMJ performance and force-time variables.